ANALYSIS OF PROJECT IMPLEMENTATION SCHEDULE USING MICROSOFT PROJECT (Case Study: Trenggalek City Square Area) - Muhammad Zainal Muttaqin; Farida Hardaningrum (NAROTAMA UNIVERSITY, 2019)
A project implementation schedule can be said to be successful if the implementation process can be completed in accordance with the planned time. Planning a good project implementation schedule must be supported by good project control. Because what happens in the field is not necessarily in accordance with what has been planned. By analyzing the cost and end time of project completion, it can provide detailed project performance schedule information. In this study, the analysis of the project implementation schedule is done manually, which is to make the S curve and use the Microsoft Project 2019 program. The method used is to enter the data related to the analysis into the program, then this Microsoft project will calculate automatically according to the formulas. calculation formula that has been made, so that the calculation of the project implementation schedule analysis will be faster and more accurate. The results of the cost analysis following the price of the Trenggalek district work unit for the renovation of the City Square is IDR. 6,078,136,530. Estimated schedule in planning the S schedule time curve with Microsoft Project 2019, there is a time difference of scheduling 39 calendar days or a difference of 1 month more that can save time and costs of implementing work. At the planning stage of scheduling with an S curve of 20 weeks or 140 days, using Microsoft Project 2019, the results obtained 101 days of project completion time. In the area of ornamental plants experiencing critical trajectory, due to the end of the work that is expected to be completed and handover, so it must add workers to be on target